Feasibility of monetary union in the SADC and EAC: evidence from business cycle synchronisation - Redda, Ephrem Habtemichael; Muzindutsi, Paul-Francois (Danubius University of Galati, 2017)
Through the Association of African Central Bank Governors, in 2003, Africa committed itself to work for a single currency and common central bank by 2021. In pursuit of this grand objective, many regional trading blocs including the Southern African Development Community (SADC) and the East African Community (EAC) are involved in various economic integration activities. Forming a monetary union is a serious endeavour that needs serious and deliberate consideration. Sufficient and sound economic basis, such as similar economic structures, should be in place. The purpose of this paper was to assess the feasibility of monetary union in the SADC and EAC by determining the similarities of the economic structures in the regions through business cycle synchronisation. This study uses annual real GDP of each country in the two regions for a period of 30 years. The results of ccorrelation analysis and T-Y Granger causality test suggest that there is overwhelming lack of business cycle synchronisation in the two economic regions, suggesting that it is not feasible to form a monetary union in these two economic regions as envisaged in the timeframe. The two economic regions, therefore, need to set and coordinate major macroeconomic policies to harmonise and achieve sustainable economic development goals in their respective regions.
Keywords: SADC; EAC; monetary union; single currency; business cycle synchronisation